(3EOGQI GdHfhc GdJLGQjI (B:s (3eONd GJNGP GdbQGQGJ (B/s - (3gfOi , efjQ GHQGgjes ((3GdGScfOQjI(B: s (3GdecJH GdYQHj GdMOjK(B, s, 2006)
(3eGgjI GdHfhc GdJLGQjI h JfXjegG h JfGhd GdHfc GdTGed h YdGbI GdHfhc GdJLGQjI HGdHfc GdeQcRj ceG Je GdJWQb Gdi ESJQGJjLjI JfejI GdehGQO GdeGdjI h GSJQGJjLjI JfejI GdhOGFY eY JfGhd ESJQGJjLjGJ dG JJWdH ehGQO eGdjI h GdJWQb Gdi SjGSI GdGbJQGV h SjGSGJ GdGSJKeGQ aj GdChQGb GdeGdjI ceG Je GdJWQb Gdi CgOGa eMaXI GdHfc h GdSjGSGJ GdJj JMce EOGQI GdeMaXI h CNjQG GdQbGHI GdeSHbI Ydi GfTWI GdHfc h GdQbGHI GddGMbI Ydi fTGW GdHfc(B.s
(3edGMb U(B.447 (3eQGLY U(B.474s
Keywords: (3GdHfhcs; (3GdHfhc GdJLGQjIs